Changes in the southern hemisphere subtropical jet stream over the twenty first century / Muhammad Yunus Ahmad Mazuki - Muhammad Yunus, Ahmad Mazuki (2016)

(untitled)
This study focuses on the historical and projected changes in the strength and meridional location of the Southern Hemisphere Subtropical Jet (STJ) using the output of Coupled Model Intercomparison Project Phase 5 (CMIP5) models. CMIP5 model output forms the basis of the Intergovermental Panel on Climate Change (IPCC) Fifth Assessment Reports (AR5). The study consists of three parts. The first part is to assess the ability of the selected CMIP5 models in simulating the historical variability of STJ. The second part is to investigate how the CMIP5 models simulate the impacts of El Niño-Southern Oscillation (ENSO) on STJ. The third part is to examine the projected changes in the strength and meridional location of STJ in 21st Century. In the first part, ERA-Interim reanalysis data is used to evaluate the historical simulation of STJ by 18 selected CMIP5 models for the period 1979 – 2012. Based on the climatology of the STJ from ERA-Interim, the area of study was selected as 70 °E to 290°E, 20°S to 40°S, and between the heights at 300 hPa and 100 hPa which is over the Indian and Southern Pacific Oceans. Southern Hemispheric winter period (June, July, August) was selected for the study since STJ is strongest and well-defined during the period. Analysis based on ERA-Interim shows that STJ weakens at the rate of 0.176 ms-1decade-1 and shifts polewards at 0.10 °decade-1, however both trends are not significant. Historical simulations of STJ by the CMIP5 models show a wide range of trends in strength and meridional location of STJ, with a multi-model mean of 0.42 ms-1decade-1 strengthening and 0.04°decade-1 equatorward shift respectively. In contrast to the ERA-Interim analysis, 94% of the CMIP5 models show a strengthening of STJ in the historical simulation. Variability of the jet strength in each individual CMIP5 model is significantly (p≤0.05) linked to the sea surface temperature changes over the eastern tropical Pacific. Second part of the study involved the assessment of the ability of the CMIP5 models in simulating ENSO effects on STJ. Results show that 47% of the CMIP5 models used in this study were able to simulate ENSO impacts realistically in terms of observed pattern. However, the models perform poorly in reproducing the observed changes in the intensity of STJ. Last part of the study consists of CMIP5 model projections with Representative Concentration Pathways (RCP) 4.5 and 8.5 to analyse the changes of the STJ for the period 2011 – 2099. The multi-model mean trend of the 18 CMIP5 models project a statistically significant (p≤0.05) increase in STJ strength at the rate of 0.29 ms-1decade-1 and 0.60 ms-1decade-1 by 2099 for respective RCP 4.5 and RCP 8.5 scenarios. Also, the mean meridional location of STJ is projected to shift poleward by 0.006°decade-1 and 0.042°decade-1 by 2099 for respective RCP 4.5 and RCP 8.5 scenarios. However, this trend is significant (p ≤ 0.05) only in RCP 8.5 scenario.